In vitro bioaccessibility and antioxidant properties of edible bird's nest following simulated human gastro-intestinal digestion - Yida, Zhang; Imam, Mustapha Umar; Ismail, Maznah (BioMed Central, 2014)
Background: Edible birds’ nest (EBN) is reported to be antioxidant-rich. However, the fate of its antioxidants after oral consumption is not yet reported. To explore this, we hypothesized that EBN antioxidants are released from their matrix when subjected to in vitro simulated gastrointestinal digestion. Methods: EBN samples were extracted using hot water (100°C) with or without subsequent sequential enzymatic digestion using pepsin (10,000 units), pancreatin (36 mg) and bile extracts (112.5 mg). Additionally, pH changes (8.9 to 2 and back to 8.9) similar to the gut were applied, and a 10 KDa dialysis tubing was used to simulate gut absorption. The antioxidant capacities of the water extracts of EBN before and after digestion were then determined using ABTS and oxygen radical absorbance capacity (ORAC) assays, while the protective effects of the EBN samples against hydrogen peroxide-induced toxicity in HEPG2 cells were determined using MTT assay and acridine orange (AO)/propidium iodide (PI) staining. Results: Antioxidant assays (ABTS and ORAC) showed that the undigested EBN water extract had little antioxidant activity (1 and 1%, respectively at 1000 μg/mL) while at similar concentrations the digested samples had significantly (p < 0.05) enhanced antioxidant activities, for samples inside (38 and 50%, respectively at 1000 μg/mL) and outside (36 and 50%, respectively at 1000 μg/mL) the dialysis tubing, representing absorbed and unabsorbed samples, respectively. Cell viability and toxicity assays also suggested that the EBN extracts were non-toxic to HEPG2 cells (cell viabilities of over 80% at 1000 μg/mL), while AOPI showed that the extracts protected HEPG2 cells from hydrogen peroxide induced-toxicity. Conclusions: Based on the findings, it is likely that EBN bioactives are released from their matrix when digested in the gut and then absorbed through the gut by passive-mediated transport to exert their functional effects. However, there is need to confirm these findings using in vivo systems to determine their clinical significance.